2015
DOI: 10.5539/eer.v5n1p110
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Inorganic Membranes for Hydrocarbon Separation from N2 for Environmental Applications

Abstract: This paper reports the preparation and characterization of a tubular alumina and silica membrane for propylene (C 3 H 6 ) and nitrogen (N 2 ) separation. Dip-coating technique was employed to prepare silica membrane. Nitrogen adsorption measurements reveal that this membrane possesses mesostructure with pore diameter of 3.940 nm and BET surface of 0.484 m 2 /g. Scanning electron microscopy (SEM) studies show that the layers are defect free and energy diffraction X-ray analysis (EDXA) confirms the compositional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It has also been reported that the bands that appeared in the spectra (400-1200 cm À1 ) characterized the metallic connection M-O-M, O-M-O or M-OH (where in this case M = Zr or Ti). 79 The strong absorption band at 594 cm À1 can be assigned to the vibrations of the Zr-O or Ti-O functional groups, but separate elucidation of bands related to Zr-O-Ti, Zr-O-Zr or Ti-O-Ti is not possible for mixed compositions. Finally these results suggest that the existence of interfacial contact between ZrO 2 , TiO 2 and rGO can lengthen the lifetime of photo-generated electron-hole pairs and thereby enhance the photocatalytic activities of GT and GTZ-20 composites.…”
Section: Papermentioning
confidence: 99%
“…It has also been reported that the bands that appeared in the spectra (400-1200 cm À1 ) characterized the metallic connection M-O-M, O-M-O or M-OH (where in this case M = Zr or Ti). 79 The strong absorption band at 594 cm À1 can be assigned to the vibrations of the Zr-O or Ti-O functional groups, but separate elucidation of bands related to Zr-O-Ti, Zr-O-Zr or Ti-O-Ti is not possible for mixed compositions. Finally these results suggest that the existence of interfacial contact between ZrO 2 , TiO 2 and rGO can lengthen the lifetime of photo-generated electron-hole pairs and thereby enhance the photocatalytic activities of GT and GTZ-20 composites.…”
Section: Papermentioning
confidence: 99%